2018
DOI: 10.1590/0034-7167-2017-0135
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived health and clinical-functional vulnerability of the elderly in Belo Horizonte/Minas Gerais

Abstract: Perceived health status influences the morbidity and mortality of the elderly. Mood disorders and recent hospitalizations directly interfere with active aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 18 publications
2
18
2
16
Order By: Relevance
“…The current study showed another essential finding: the association of the outcome variable with depressive symptoms, a result also reported in the national literature 1,3,8,26,27,35,36 , as well as in the already mentioned studies conducted in Shanghai 12 , in Germany 14 , in Santiago de Cali 16 and the Republic of Latvia 28 . We emphasize that the poor evaluation of one's health can be seen as a depressive symptom 36 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The current study showed another essential finding: the association of the outcome variable with depressive symptoms, a result also reported in the national literature 1,3,8,26,27,35,36 , as well as in the already mentioned studies conducted in Shanghai 12 , in Germany 14 , in Santiago de Cali 16 and the Republic of Latvia 28 . We emphasize that the poor evaluation of one's health can be seen as a depressive symptom 36 .…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence values of this outcome swing in the literature, with the following records of findings: from 12.6 to 51.9% in a systematic review on the self-perception of health by Brazilian elderly 3 ; 57.5% in a large municipality of MG 9 ; 51.2% in Florianópolis-SC 10 ; 49.6% in a survey carried out in three Brazilian cities 7 ; 10.9% in Campinas-SP 6 . The prevalence was higher in a reference center in Belo Horizonte-MG, at 70.1% 26 . In other countries, findings were as follows: in Germany, 62.5% of the elderly reported negative self-perception of health 14 ; in Shanghai, China, the proportion was 56.8% 12 ; while in Santiago de Cali, Colombia, the prevalence was 40.1% 16 .…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, our sample is mainly composed of recent immigrants, a situation that is known to be associated in Canada with poor social determinants of health [3]. Numerous authors have previously shown that low social position is a risk factor for health [37,55,58]. In our study, negative perception of health was higher among respondents who declared insufficient family income.…”
Section: Plos Onementioning
confidence: 62%
“…We assessed variables associated with the main dependent variable (self-perceived health). We dichotomize our main dependent variable into two categories: bad/fair (negative self-perceived health status) vs good/ very good/ excellent (positive self-perceived health status) [31,58]. Guided by the Social Determinants of Health conceptual framework of The World Health Organization [59], the following independent variables were assessed as potential correlates of negative self-perceived health status: structural determinants that relates to social position (socioeconomic status, migration status, gender, region of birth); and intermediary determinants related to working conditions (work contract, occupational injury), material circumstances (food security, insalubrious housing (measured as at least one of the following situation: presence of cockroaches, bedbugs, mice, rats, smell or spots of mold, water infiltration, flooding or water damage, or other situation), psychosocial factors (social support, discriminations, mental distress, stressors and fear related to migration status), health issues (in the past 12 months) and access to the health system (unmet health care needs, number of years without medical insurance).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is known that negative self-perception of health is related to adverse outcomes in old age such as disability and mortality (19,20) . In a study (21) with a sample of older adults from Belo Horizonte, Minas Gerais, Brazil, attended to at a Reference Center in elderly care, at the secondary health care level, obtained a prevalence of 70.1% (n=218) of negative self-perception of health and evidenced that this was associated with impaired autonomy and independence.…”
Section: Discussionmentioning
confidence: 99%